A game theory approach to online lead generation for oligopoly markets. (July 2018) - Zutshi, Aneesh; Mota, Diogo; Grilo, Antonio; Faias, Marta
Highlights: A management model based on game theory is proposed. The model estimates the quantity of online generated leads efficiently. A mathematical formulation of the generalized model is proposed. An application scenario is formulated and its results analyzed. The Nash and Stackelberg equilibria are obtained and discussed. Abstract: Digital marketing has received much attention from most firms recently. With the increasing competition and exigency, marketing managers' need for reliable and scientifically supported decision systems to assist them has never been greater. This paper presents a management model for estimating the quantity of online leads they should generate in a given period of time in order to achieve their goal, measured in terms of contracts gained in the most effective and efficient way possible. Through the application of Game Theory, the strategies of the rival firms are taken into account to provide marketing managers with a set of reliable possible decisions that can provide a competitive advantage. Results show a clear improvement of the effectiveness and efficiency of the decisions. In certain scenarios, an increase in the quantity of online generated leads by a firm leads to a positive impact on the firm's and the competitors' sales. Results obtained from the Nash and Stackelberg equilibria show that the Stackelberg equilibrium is more efficient, given the higher expected profits it derives and the follower in the Stackelberg equilibrium yields a higher expected profit than the leader or first mover.